Energy Saving as Key Factor for Increasing Country’s Energy Security - E. P. Korsak; V. A. Nadomin (Наука и техника, 2020)
Power engineering is one of the main types of economic activity of the Republic of Belarus. The priority deve-lopment of the country’s energy sector is determined by its key role in ensuring the efficient functioning of the national economy,  stable  operation  of  the  social infrastructure, and observance of  social  norms  and  standards  for  the  population. and importance of energy resources for the development of the economy and society as a whole can hardly be overestimated because of their active influence on the intensity of production and consumption processes. Currently, the main sources of energy are oil, natural gas, coal, oil shale and nuclear energy. Economy of the Republic is very dependent on energy imports. This is a serious test for the country under conditions of constant rise in hydrocarbon prices. Belarus imports more than 90 % of oil, 100 % of natural gas and 25 % of liquefied gas and 100 % of the whole consumed coal. The energy intensity of domestic enterprise products is significantly higher than in industrialized countries. Therefore, improvement of energy efficiency is fundamental for our country. In this regard, a real economic sector depends on the stable operation of energy enterprises, timely modernization of equipment, rational use of fuel and energy resources and effective implementation of energy conservation measures. Most of the energy sector problems can be solved by improving the energy security indicators of the Republic, namely, as a result of the introduction of a range of energy-saving measures, use of secondary energy resources and development of renewable energy sources.